LOW RANK COAL FORMASI SAJAU DAERAH TELUK SEMANTING DAN TANJUNG BATU KECAMATAN PULAU DERAWAN, KABUPATEN BERAU – KALIMANTAN TIMUR - -, Geni Dipatunggoro (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
The studied area belong to Teluk Semanting vilage and Tanjung Batu vilage, Pulau Derawan District, Berau Regency, East Kalimantan Province.Coal Bearing Formation is Sajau Formation with the younger from Latih Formation at PT. Berau Coal mine, description is black, vitreous luster, subconcoidal fracture, very hard to soft, brown streak, is general resin and piryt and sometimes wood structure. Phisycal is based on Sub Bituminus B Coal. Outcrop is followed the folded wich North West – South East, the range of strike N300ºE – N00ºE and N120ºE – N170ºE. The dip of coal is 8ºNE - 28ºNE and 5ºSW - 13ºSW.Indicated reserve of coal at study area is based on resources calculating with make use of the regional geologic explanation has reached 136 million ton, This reserve belong to the middle of the big mining.Quality of coal at study area with the measured parameter is “inherent Moisture” =10,20%-14,58,8%, Ash = 1,10%-7,61%, “Volatile Matter” = 36,58%-45,49%, “Fixed Carbon” = 37,50-45,72%, “Total Sulphur” = 0,12%-2,86%, Calorivic value the range = 5.666 – 6.427 Kkal/kg.